Hepatocyte-specific IKK-β activation enhances VLDL-triglyceride production in APOE*3-Leiden mice - van Diepen, Janna A. (The American Society for Biochemistry and Molecular Biology, 2011)
Low-grade inflammation in different tissues, including activation of the nuclear factor κB pathway in liver, is involved in metabolic disorders such as type 2 diabetes and cardiovascular diseases (CVDs). In this study, we investigated the relation between chronic hepatocyte-specific overexpression of IkB kinase (IKK)-β and hypertriglyceridemia, an important risk factor for CVD, by evaluating whether activation of IKK-β only in the hepatocyte affects VLDL-triglyceride (TG) metabolism directly. Transgenic overexpression of constitutively active human IKK-β specifically in hepatocytes of hyperlipidemic APOE*3-Leiden mice clearly induced hypertriglyceridemia. Mechanistic in vivo studies revealed that the hypertriglyceridemia was caused by increased hepatic VLDL-TG production rather than a change in plasma VLDL-TG clearance. Studies in primary hepatocytes showed that IKK-β overexpression also enhances TG secretion in vitro, indicating a direct relation between IKK-β activation and TG production within the hepatocyte. Hepatic lipid analysis and hepatic gene expression analysis of pathways involved in lipid metabolism suggested that hepatocyte-specific IKK-β overexpression increases VLDL production not by increased steatosis or decreased FA oxidation, but most likely by carbohydrate-responsive element binding protein-mediated upregulation of Fas expression. These findings implicate that specific activation of inflammatory pathways exclusively within hepatocytes induces hypertriglyceridemia. Furthermore, we identify the hepatocytic IKK-β pathway as a possible target to treat hypertriglyceridemia.